The Influence of Accompanying Music on Performance Mediated by Variables of Comfort, Motivation, and Satisfaction - Cahyani, Diah; Negoro, Anis Sirojuddin Suryo; Sabani, Nurus (Fakultas Ekonomi Universitas Kadiri, 2025)
This study aims to analyze the influence of musical accompaniment on mediated performance variables: comfort, motivation, and job satisfaction. This research adopts a descriptive-exploratory approach. The study was conducted at PT Lion Super Indo DC Mojokerto. The population consists of 92 employees, and thus this study employs total sampling. Data collection was carried out using a questionnaire, and data analysis was performed using SmartPLS version 3.3.7. Hypothesis testing involved comparing T-Statistics and P-Values. The results of the study indicate that: musical accompaniment has a significant influence on job comfort, musical accompaniment has a significant influence on job satisfaction, musical accompaniment has a significant influence on motivation, musical accompaniment does not have a direct influence on mediated performance variables of job comfort, musical accompaniment does not have a direct influence on mediated performance variables of job motivation, and musical accompaniment does not have a direct influence on mediated performance variables of job satisfaction.